Distinct electronic structure of the electrolyte gate-induced conducting phase in vanadium dioxide revealed by high-energy photoelectron spectroscopy - Karel, Julie; Violbarbosa, Carlos E.; Kiss, Janos; Jeong, Jaewoo; Aetukuri, Nagaphani; Samant, Mahesh G.; Kozina, Xeniya; Ikenaga, Eiji; Fecher, Gerhard H.; Felser, Claudia; Parkin, Stuart S. P. (ACS nano, 2014)
The development of new phases of matter at oxide interfaces and surfaces by extrinsic electric fields is of considerable significance both scientifically and technologically. Vanadium dioxide (VO2), a strongly correlated material, exhibits a temperature-driven metal-to-insulator transition, which is accompanied by a structural transformation from rutile (high-temperature metallic phase) to monoclinic (low-temperature insulator phase). Recently, it was discovered that a low-temperature conducting state emerges in VO2 thin films upon gating with a liquid electrolyte. Using photoemission spectroscopy measurements of the core and valence band states of electrolyte-gated VO2 thin films, we show that electronic features in the gate-induced conducting phase are distinct from those of the temperature-induced rutile metallic phase. Moreover, polarization-dependent measurements reveal that the V 3d orbital ordering, which is characteristic of the monoclinic insulating phase, is partially preserved in the gate-induced metallic phase, whereas the thermally induced metallic phase displays no such orbital ordering. Angle-dependent measurements show that the electronic structure of the gate-induced metallic phase persists to a depth of at least ∼40 Å, the escape depth of the high-energy photoexcited electrons used here. The distinct electronic structures of the gate-induced and thermally induced metallic phases in VO2 thin films reflect the distinct mechanisms by which these states originate. The electronic characteristics of the gate-induced metallic state are consistent with the formation of oxygen vacancies from electrolyte gating. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: ionic liquid electrolyte gating; orbital polarization; X-ray photoelectron spectroscopy